Science Learning Based On Ethnoscience: Exploring Local Wisdom As A Learning Resource In Elementary School - Rabiatun Adawiah; Salwa Nur Sapiatun Nakjah; Fitri Muslihatun (Indonesian Journal of Elementary and Childhood Education, 2026)
Natural science learning in Elementary School currently faces various challenges, such as teachers’ difficulties in developing ethnosciences-based learning resources. This study aims to identify, evaluate, and synthesize the utilization of local wisdom as a source for science learning at the elementary level using a systematic literature review (SLR) approach. The analysis was conducted on 21 reputable scientific articles from 2016 to 2025 relevant to the theme of ethnoscience. The findings indicate that various forms of local wisdom, including those based on the environment and nature, food processing and traditional products, arts, culture and local traditions, as well as traditional games and technology, contain elementary science content ranging from mechanics, thermodynamics, matter and its changes, sound and light, ecosystems, the human body, and plant structures. The integration of the material is implemented through laboratory manuals, e-modules, modules, student worksheets (LKPD), illustrated storybooks, digital posters, and educational game media. These tools are significantly proven to enhance students’ cognitive abilities (conceptual understanding, scientific literacy, critical thinking, problem solving, and creative dimensions), affective domains (motivation, interest, and cultural awareness), and psychomotor skills (science process skills). The study concludes that ethnoscience is an approach capable of realizing more interactive and meaningful science learning.